UV-Vis Luminescence imaging techniques/ Técnicas de imagen de luminiscencia UV-Vis - Fuster López, Laura (Conservation 360, 2020)
Ever since its first introduction in the field of conservation, the role of UV-VIS luminescence/fluorescence (UVL and UVf, respectively) imaging has been expanding.The unique and significant contribution of this technique for investigation of cultural heritage has led to the development of new methodologies and applications. Each chapter in this volume can be read independently. While this means that some repetition may occur between the individual chapters, in particular regarding the explanation of terminology and methodology, such overlap provides interesting opportunities for cross-comparison of both terminology and methodology. In addition, it highlights similarities and differences between different situations in the practical application